2019
DOI: 10.1021/acsami.9b13358
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of an RGO/MoS2/Pd 2D Heterostructure for Electrocatalytic Overall Water Splitting in Alkaline Medium

Abstract: To achieve sustainable production of H2 at ambient temperature, highly active and stable electrocatalysts are the key to water splitting technology commercialization for hydrogen and oxygen production to replace Pt and IrO2 catalysts. Herein, a modified interface of palladium (Pd) and reduced graphene oxide (RGO)-supported molybdenum disulfide (MoS2) prepared by the solvothermal followed by chemical reduction method is established, in which abundant interfaces are formed. The phase structure, composition, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…The lowest Tafel slopes of MoS 2 @CNF (i.e., 41 mV dec –1 ) and MoS 2 @GC (i.e., 71 mV dec –1 ) as compared to CNF (i.e., 148 mV dec –1 ) and GC (i.e.,195 mV dec –1 ) advocate for the faster kinetics of the fabricated catalysts. The graphitic carbon present on the spent catalyst decreases the interlayer stacking of MoS 2 , resulting in exposed edge sites; furthermore, the transport of charges via the basal plane of MoS 2 is also favored, 62 while in the case of MoS 2 @CNF, the electrocatalytic activity is improved due to the additional surface area of the fibers, providing more vacancy for water to adsorb, dissociate, and release oxygen and showing less affinity toward OH – . 58 The highest exchange current densities revealed by MoS 2 @CNF (i.e., i ° = 2.11 mA cm –2 ) and MoS 2 @GC (i.e., i ° = 1.92 mA cm –2 ) when compared to those of CNF ( i ° = 1.35 mA cm –2 ) and GC ( i ° = 0.385 mA cm –2 ) show that the interfacial barrier for charge transfer is decreased due to which the kinetics of the OER is significantly improved.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest Tafel slopes of MoS 2 @CNF (i.e., 41 mV dec –1 ) and MoS 2 @GC (i.e., 71 mV dec –1 ) as compared to CNF (i.e., 148 mV dec –1 ) and GC (i.e.,195 mV dec –1 ) advocate for the faster kinetics of the fabricated catalysts. The graphitic carbon present on the spent catalyst decreases the interlayer stacking of MoS 2 , resulting in exposed edge sites; furthermore, the transport of charges via the basal plane of MoS 2 is also favored, 62 while in the case of MoS 2 @CNF, the electrocatalytic activity is improved due to the additional surface area of the fibers, providing more vacancy for water to adsorb, dissociate, and release oxygen and showing less affinity toward OH – . 58 The highest exchange current densities revealed by MoS 2 @CNF (i.e., i ° = 2.11 mA cm –2 ) and MoS 2 @GC (i.e., i ° = 1.92 mA cm –2 ) when compared to those of CNF ( i ° = 1.35 mA cm –2 ) and GC ( i ° = 0.385 mA cm –2 ) show that the interfacial barrier for charge transfer is decreased due to which the kinetics of the OER is significantly improved.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al [195] used the advantageous vertical growth method to prepare MoS2/CoS2 catalysts. The heterojunction catalyst RGO/MoS2/PD was prepared by Pandey et al [196]; during the heterojunction formation process, a phase transition was observed. The combined effects of the heterojunction interlayer, phase transition, and metal doping resulted in improved HER activity [196].…”
Section: Formation Of Heterostructurementioning
confidence: 99%
“…Transition‐metal‐based catalysts (e. g., oxides, phosphides, chalcogenides, and carbonitrides) have attracted tremendous interest in recent years owing to their impressive OER activities, natural abundance, and the consequent low costs [20–22] . Among these, transition‐metal phosphides (TMPs) are considered to be one of the most studied electrocatalytic materials at present [23–25] . However, monometal TMPs usually have poor electroconductivities and inferior stabilities, thus significantly limiting their expected catalytic activities [26–28] .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Among these, transition-metal phosphides (TMPs) are considered to be one of the most studied electrocatalytic materials at present. [23][24][25] However, monometal TMPs usually have poor electroconductivities and inferior stabilities, thus significantly limiting their expected catalytic activities. [26][27][28] For this reason, multicomponent TMPs have been developed and have proven to be feasible alternatives for enhancing catalytic performance, both in theory and practice.…”
Section: Introductionmentioning
confidence: 99%